The Biological and Clinical Aspects of Merkel Cell Carcinoma - Koljonen, Virve; Lui, Weng-Onn; Becker, Jürgen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, we sought advanced knowledge in both basic and clinical research presented in original articles and comprehensive reviews highlighting the latest advances in MCC. Articles focus on but were not restricted to the molecular basis of the disease, translational investigations of biomarkers for prospective clinical applications, and innovative diagnostic and therapeutic approaches in MCC.